The Effect of Human Rights Rules on Private international Law In the Light of European Court of Human Rights Judgments - Reza Maghsoudi (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2016)
Human rights norms have caused some evolutions in the scope of forum conflicts, conflict of laws and recognition and enforcement of foreign judgments. Use of traditional rules in this branch of law such as unilateral conflict rules has been questioned and some ancient connecting factors, such as nationality have been periled. In the area of foreign judgments recognition, human rights regulations have also persuaded states to accept acquired rights abroad. However, necessities of public international law, states interests, human rights limits, like proportionality and public order considerations have decreased human rights effects on private international law and especially forum conflicts. In this paper we will first discuss the concept of public order and its relationship to human rights, and then human rights norms in each private international law issues will be analyzed with regard to the judgements of European Court of Human Rights